2021
DOI: 10.3892/ol.2021.13036
|View full text |Cite
|
Sign up to set email alerts
|

Research progress concerning m6A methylation and cancer (Review)

Abstract: N6-methyladenosine (m 6 A) methylation is a type of methylation modification on RNA molecules, which was first discovered in 1974, and has become a hot topic in life science in recent years. m 6 A modification is an epigenetic regulation similar to DNA and histone modification and is dynamically reversible in mammalian cells. This chemical marker of RNA is produced by m 6 A 'writers' (methylase) and can be degraded by m 6 A 'erasers' (demethylase). Methylated reading protein is the 'reader', that can recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…We also demonstrated the increased m6A modification on the 3'UTR region of the METTL4-induced PD-L1 mRNA in CCA cells. It has been documented that m6A modification affects mRNA stability, splicing, nuclear export, and/or translation of target mRNAs, depending on the distinct proteins that recognize them [e.g., YTHDF1, YTHDF2, YTHDF3 (6)]. We have shown that decreasing Siah2 mRNA levels by METTL14 were mainly due to the accelerated degradation of Siah2 mRNA, depending on the m6A reader protein YTHDF2, thereby decreasing Siah2 protein level.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We also demonstrated the increased m6A modification on the 3'UTR region of the METTL4-induced PD-L1 mRNA in CCA cells. It has been documented that m6A modification affects mRNA stability, splicing, nuclear export, and/or translation of target mRNAs, depending on the distinct proteins that recognize them [e.g., YTHDF1, YTHDF2, YTHDF3 (6)]. We have shown that decreasing Siah2 mRNA levels by METTL14 were mainly due to the accelerated degradation of Siah2 mRNA, depending on the m6A reader protein YTHDF2, thereby decreasing Siah2 protein level.…”
Section: Discussionmentioning
confidence: 68%
“…Thirteen weeks after CD34+ cell injection, CD34+ humanized NCG mice were randomly assigned into experiment groups. Indicated CCA cells with LV-NC/LV-METTL14 of 5×10 6 were injected into the right flank of CD34+ humanized NCG mice. Tumor volume was calculated by the following formula: volume = ab2/2 (a, the longer axis; b, the shorter axis).…”
Section: Cd34+ Humanized Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins may broadly be divided into 3 categories: writer complexes, m6A demethylases, and function executions (readers). Within these categories, WTAP, RBM15, RBM15B, METTL3, METTL14, METTL16, and KIAA1429 are among the writer complexes; FTO and ALKBH5, the 2 evaluated m6A demethylases, are among the erasers; HNRNPs, YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2, YTHDC3, EIF3A, IGF2BP1, IGF2BP2, and IGF2BP3 are among the function executions (readers) (23)(24)(25)(26). Recent studies have shown that m6A is required for a wide range of biological activities, including viral infection (27,28), stress (29), heat shock (30), and DNA damage (31).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Studies have proved that the abnormal regulation mechanism can induce the abnormal expression of downstream target genes and eventually lead to tumor. [10] M6A methylation is composed of methyltransferases (writers), demethylases (erasers) and m6A binding proteins (readers). [11] Once these enzymes are abnormal, they will cause a series of diseases, including cancer, neurological diseases and embryonic retardation.…”
Section: Introductionmentioning
confidence: 99%